Latino children’s narrative competencies over the preschool years - Gigliana Melzi (Actualidades en Psicología, 2013)
Narrating is a sophisticated discourse skill that emerges during the preschool years, and is both correlated with and predictive of various aspects of school performance. The existing research on children’s narrative development provides a limited snapshot of the narrative trajectories of Latino children living in the United States. The present study examined the narrative skills of 118 low-income Latino children over a two- year period. Results showed that there were signifi cant developmental changes in children’s storybook retelling skills over the preschool years. By age fi ve, children were more autonomous in their narration, produced more coherent and complex stories, and incorporated more sophisticated language in their narratives than did younger preschoolers. Further analyses identifi ed those specifi c macro- and micro-structural skills that develop during the preschool years.